Breakage of a Third Generation Gamma Nail: A Case Report and Review of the Literature - Takashi Iwakura; Takahiro Niikura; Sang Yang Lee; Yoshitada Sakai; Kotaro Nishida; Ryosuke Kuroda; Masahiro Kurosaka (Case Reports in Orthopedics)
The use of intramedullary nails to treat trochanteric fractures of the femur has increased with the increasing size of the elderly population. The third generation Gamma nail is currently one of the most popular devices for the treatment of trochanteric fractures. Nail breakage is a rare complication, possibly resulting from fatigue fracture of the implant. We present the first reported case of breakage of a third generation Gamma nail that was not used to treat a pathological fracture. An 83-year-old woman with an unstable trochanteric fracture of the femur was treated using a third generation Gamma nail. She was referred to our hospital 14 months postoperatively with nail breakage at the opening for the lag screw. The breakage was secondary to nonunion, which was thought to be mainly due to insufficient reduction of the fracture. The broken nail was removed, and the patient underwent cemented bipolar hemiarthroplasty. At followup 18 months later, she was mobile with a walker and asymptomatic with no complications. This case shows that inadequate operation such as insufficient reduction of the trochanteric fracture may result in nonunion and implant breakage, even when using a high-strength, well-designed implant.